INNOVATION MANAGEMENT CAPABILITIES AND ORGANIZATIONAL RESILIENCE AS A PREREQUISITE FOR SUSTAINABILITY OF SMES IN WUKARI NIGERIA - Ikyabo Anatasia Yinduwa; Danjuma Tsintop Ussaini; Undie Unung Philip; Kungaba Jordan (International Journal of Education, Management, and Technology, 2026)
Although SMEs are widely recognized as drivers of economic growth, employment generation, and sustainable development, their long-term viability in semi-urban and rural contexts remains underexamined. This study investigates the influence of innovation management capabilities and organizational resilience on the sustainability of SMEs in Wukari Local Government Area, Taraba State, Nigeria. Using a survey research design, data were collected from 152 SME owners and managers and analyzed through regression analysis. The findings indicate that innovation management capabilities significantly improve SME sustainability (β = 0.642, p < 0.001), accounting for 37.8% of the variance, while organizational resilience also exerts a strong positive effect (β = 0.587, p < 0.001) on long-term business viability. The results further show that SMEs in Wukari rely primarily on product innovation and anticipatory resilience, but remain relatively weak in process innovation, service innovation, and adaptive resilience. Consistent with the Resource-Based View and Dynamic Capability perspectives, the study demonstrates that internally developed capabilities are critical for sustaining SMEs in dynamic and resource-constrained environments. It concludes that SME sustainability in Wukari depends not only on strengthening innovation capacity but also on enhancing more adaptive and transformative forms of resilience. This study contributes to the SME sustainability literature by providing context-specific evidence from a semi-urban Nigerian setting and by identifying strategic priorities for SME owners, policymakers, and financial institutions seeking to improve innovation support and risk-management capacity.